2005
DOI: 10.1093/humrep/dei068
|View full text |Cite
|
Sign up to set email alerts
|

Serum and follicular fluid levels of soluble Fas, soluble Fas ligand and apoptosis of luteinized granulosa cells in PCOS patients undergoing IVF

Abstract: Decreased serum levels of sFas and luteinized granulosa cell DNA fragmentation is observed in patients with PCOS undergoing IVF cycles. Metformin therapy preceding IVF demonstrates an antiapoptotic effect with increased serum levels of sFas, decreased follicular fluid levels of sFasL and prevention of luteinized granulosa cell DNA fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 23 publications
3
26
3
1
Order By: Relevance
“…3), indicates significant apoptosis in Groups A and B. Apoptotic changes in the present study are further supported by the significant increase in DNA damage observed in Group A and B compared to Group C. These findings are in agreement with reports of Saito et al [2002] where they have documented increased levels of apoptotic cells in endometriosis. In another study, excessive luteinized DNA fragmentation in GC of PCOS patients undergoing IVF cycles is documented [Onalan et al 2005]. IVF outcome parameters including fertilization rate, good quality embryo formation rate, and pregnancy outcome were adversely affected in Group B (Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…3), indicates significant apoptosis in Groups A and B. Apoptotic changes in the present study are further supported by the significant increase in DNA damage observed in Group A and B compared to Group C. These findings are in agreement with reports of Saito et al [2002] where they have documented increased levels of apoptotic cells in endometriosis. In another study, excessive luteinized DNA fragmentation in GC of PCOS patients undergoing IVF cycles is documented [Onalan et al 2005]. IVF outcome parameters including fertilization rate, good quality embryo formation rate, and pregnancy outcome were adversely affected in Group B (Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…They think that low levels in this apoptotic marker imply increased apoptosis and possibly a downregulation of the immune system of patients. Onalan et al reported that low levels of serum sFas in patients with PCOS compared to male factor infertility group [20]. But they didn't found any significant difference in terms ofFF of sFas and sFasL, serum sFasL in these groups.…”
Section: Discussionmentioning
confidence: 93%
“…Cumulus and granulosa cells are the major source of estradiol. For PCOS patients, the apoptosis level is increased in granulosa cells [26]. Moreover, PCOS granulosa cells, unlike normal granulosa cells, show a limited capacity to synthesize progesterone, either spontaneously or in response to follicle-stimulating hormone (FSH) stimulation [27].…”
Section: Introductionmentioning
confidence: 99%